Inspiring disruptive change: A novel approach to modelling the value creation process - Manuel Au-Yong Oliveira (2010)
This methodology paper puts forth a novel process with which to portray the value network and enterprise asset creation. Real cases which involved field research by the authors are used to present and better illustrate certain concepts. Organizations involve intense human interaction and require novel ways which make evident variations in performance, a central aspect of management today and in the near future. Our contribution is in combining the use of the narrative / storylines, game design patterns, value network analysis and the dynamic capabilities paradigm to reduce the complexity of the strategy debate. Our modelling tool is also pictorial and so simple to grasp. The primary value of graphical notations lies in their communication and understanding possibilities (Fowler, 2004). The importance of the dynamic capabilities paradigm (Teece et al., 1997) is emphasized in which ICT plays a central and strategic role (Pavlou, 2004) in the creation of value and consequently enterprise assets. Geertz (2000) brought attention to the fact that research is performed in order to clarify or usefully revise our own or someone elses ideas and we see this clarification and revision as being necessary given a heightened need to motivate and inspire people to carry out actions of disruptive change (Denning, 2004).